Pengaruh Harga dan Kualitas Pelayanan terhadap Kepuasan Pelanggan pada Toko Aureola Beauty di Sukoharjo - Dania Oktavianita Sari; Khabib Alia Akhmad; Nur Hadi (Jurnal Manajemen Riset Inovasi, 2026)
This study aims to analyze the effect of price and service quality on customer satisfaction at Aureola Beauty Store in Sukoharjo. The research employed a quantitative approach using a causal associative method. The population consisted of Generation Z customers who had made purchases at Aureola Beauty Store. The sampling technique used was purposive sampling, with a total sample of 100 respondents. Data were collected through questionnaires using a 4-point Likert scale. Data analysis was conducted using SPSS version 27, including validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, ttest, F-test, and coefficient of determination (R²).The results indicate that price has a positive and significant effect on customer satisfaction, with a t-value of 3.045 and a significance value of 0.003 < 0.05. Service quality also has a positive and significant effect on customer satisfaction, with a t-value of 7.218 and a significance value of 0.000 < 0.05. Simultaneously, price and service quality have a positive and significant effect on customer satisfaction, as evidenced by an F-value of 57.931 and a significance value of 0.000 < 0.05. The coefficient of determination (R²) of 0.544 indicates that 54.4% of customer satisfaction can be explained by the variables of price and service quality, while the remaining 45.6% is influenced by other factors not examined in this study.